Egg donation in Peru: two years of experience. First results of in vitro fertilization with donated oocytes Embryonic Transference - Noriega, Luis (2015)
OBJECTIVE: To determine the results of oocyte donation in our experience. MATERIAL AND METHODS: Sixteen cycles of oocyte donation were performed between June 1995 and May 199 7 in 16 patients aged 35 through 48. Indications were perimenopause and/or diminished ovarian reserve (14 cases) and surgical castration (2 cases). Hormonal replacement therapy was given to receptors and ovarian stimulation by large protocol to donors. RESULTS: Seventy-one oocytes were inseminated, producing 60 formed pre-embryos, afertilization rate of 84,2%, Average insemination was 4,4 oocytesper cycle. We obtained 6 clinical pregnancies and apregnancy rate of 3 7,5%. CONCLUSIONS: Oocyte donation program used for the first time in our country obtains the highest pregnancy rates.